DEVELOPMENT OF INSECTICIDE PREPARATION "ENTOVANT" - Bektemirov Azizbek Obitali ugli; Ikramova Maftuna Mardonzhonovna; Hoshimov Farhod Fayzullaevich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article presents the results of the development of the insecticidal preparation Entovant 15% c.s. by mixing the active substance with surfactants and other components.